Paquirea A New Andean Genus for Chucoa lanceolata (Asteraceae) - Panero, Jose L. (2013)
A previous molecular study showed that Chucoa ilicifolia, the type species of the genus Chucoa, is within the genus Onoseris clade. A new genus, Paquirea Panero & S.E. Freire, is proposed and described to accommodate the other species of Chucoa, C. lanceolata, as Paquirea lanceolata (H. Beltrán & Ferreyra) Panero & S.E. Freire, comb. nov. The new genus differs from Onoseris in having actinomorphic corollas with lobes of equivalent size and discoid capitula. Paquirea shares with other Onoserideae a shrubby habit, solitary capitula, epaleate receptacles, fivelobed corollas, anthers with long tails, style branches dorsally papillose with rounded apices, and heteromorphic pappi in three series. Among the Onoserideae, Paquirea, because of its solitary capitula and shrubby habit, is most similar to Plazia and Aphyllocladus. Paquirea can be distinguished from these genera by its conspicuously leafy stems (vs. leaves soon deciduous in Aphyllocladus), alternate leaves (vs. spirally-arranged leaves in Plazia), discoid capitula (vs. radiate capitula in Plazia), cream-colored corollas (vs. lilac to purple corollas in Aphyllocladus and white to pink in Plazia), and glabrous achenes (vs. long-pilose achenes in Aphyllocladus). A key and a comparative table to the seven genera of Onoserideae are also provided.